Pola Perubahan Fonem Vokal dan Konsonan Kata Serapan dari Bahasa Jepang ke dalam Bahasa Indonesia - Putri, Mellati Riandi; Fachrullah, Tb. Ace; Machdalena, Susi (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2021)
This research is purposed to determine the pattern of phoneme which changed in Indonesian loanwords which derived from Japanese. This research based on descriptive qualitative analysis method. The data source of this research is article from Kompas news online website which uploaded from January until October 2020. There are 67 data which classified to the pattern of phoneme that changed based on theory of vowels and consonant from Marsono and for Japanese vowels and consonant using theory from Sudjianto and Dahidi. There are 3 patterns of phoneme that changed in Indonesian loanwords which derived from Japanese found from this research: the pattern from one vowel change, the pattern from one vowel and one consonant change, and the pattern from one consonant change. The further research through big data such as corpus based research might be needed to find another variations of this pattern.